Fast widefield scan provides tunable and uniform illumination optimizing super-resolution microscopy on large fields - Adrien Mau (Nature Portfolio, 2021)
Uniform illumination is a prerequisite for quantitative analyses in both classical fluorescence microscopy and single molecule localisation microscopy. Here, the authors introduce ASTER, an illumination technique that generates uniform illumination over large and adaptable fields of view, compatible with epifluorescence, HiLo and TIRF illumination schemes.